Recurrence of Snow falling in lraq For Geographic Analysis - Assis. Lectu. Ahmed Alwan Hamza Saeed (Journal of College of Education, 2025)
The research aims to find out one of the types of precipitation, which is snowfall, which occurs in the form of fine crystals of ice occur in the cold season after condensation occurs at certain heights in the gaseous envelope and snowfall occurs after the inability of air currents to carry solid particles and heavy water droplets in the climate of barren flat surfaces in Iraq and snow, which consists of blocks of ice crystals,  It grows directly from water vapor in the air when the air temperature below freezing in the middle stratigraphic clouds or stratigraphic weights is below the freezing point. The study found that thestudy found that the frequency of snow varied from year to year and according to the months between climatic stations, where the highest frequency of snow was recorded on the wet station and the reason is that the station is under the influence of the recurrence of cold atmospheric heights, which is the main reason for the drop in temperatures below zero Celsius, but in the Amara station did not witness any recurrence of snowfall during the study period due to the distance of the station from the effects of cold polar masses affecting the country during the winter. The study also found that snowfalltudy period due to the distance of the station from the effects of cold polar masses affecting the country during the winter. The study also found that snowfall depends in its composition on low temperatures without.
Keywords: Condensation, Analysis Geographic ، Snowfall